ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMSI FAST FOOD PADA REMAJA - Mhd Abdul Rajab Harahap; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
Fast food is a type of food that has been processed and then produced for further resale with a fast service process. Fast food is available quickly and ready to eat such as flour fried chicken, pizza, burgers, french fries, pasta, nuggets, sausages, fried foods and so on. In this study using research methods qualitative research methods. Collecting data in this study is by conducting interviews with several related parties. From the results of the study it was stated that there were 4 factors that influenced the consumption of fast food in adolescents. Factors that influence fast food consumption patterns in adolescents are friendship, social media, place of residence and pocket money. It can be concluded that teenagers consume fast food more often than eat healthy food. This is due to several supporting factors that encourage teenagers to prefer fast food. Teenagers have an allowance factor in consuming fast food which states that most of them buy fast food more than anything else.